Using SaTScan to identify and map nightlife areas in Philadelphia, PA - Eliza W. Kinsey; Kathryn M. Neckerman; James W. Quinn; Michael D. M. Bader; Stephen J. Mooney; Gina S. Lovasi; Dirk Kinsey; Andrew G. Rundle (Journal of Maps)
Many cities have promoted nightlife or entertainment districts – concentrations of restaurants, bars, and other entertainment-related businesses – in order to revitalize declining neighborhoods. While entertainment districts can boost economic growth, they can also contribute to public health risks including violent crime, traffic accidents, and other harms. With data from the National Establishment Time Series (NETS) business database, we developed methods to use SaTScan cluster detection software to identify entertainment districts, and applied the method in a case-study of Philadelphia, Pennsylvania. Using SaTScan, we identified and mapped 101 spatial clusters of entertainment businesses in the city. Our approach is scalable and does not require prior local knowledge about entertainment areas. The results add to a small but growing literature about the use of SaTScan to map neighborhood features. Placing entertainment districts in spatial context can inform how the built environment might amplify or minimize the potential health risks of these districts.